A reliability study concerning the acoustic simulations of timber elements for buildings. (10th January 2022) - Caniato, M.; Gasparella, A.; Bettarello, F.; Santoni, A.; Fausti, P.; Granzotto, N.; Bécot, F.X.; Chevillotte, F.; Jaouen, L.; Borello, G.; Robin, O.; Atalla, N.
Highlights: An international round robin test is performed on timber elements. Acoustic methods and approaches are compared between each other. Measurements are made to compare simulated results. No available methodology is able to fully simulate a timber element. Further materials characterizations are needed to improve acoustic simulations. Abstract: Engineered wood constructions and timber buildings are rapidly developing, while the numerical techniques usable for their sound insulation properties are various and often still under development. This research constitutes a first step towards the reliability determination of building acoustics simulations on timber-based elements. A small scale round robin involving five research laboratories is presented. The results obtained show significant deviations depending on the chosen numerical method and indicate how laboratory measurements could not be approximate with a good accuracy. Finally, a sensitivity analysis is presented and challenges as well as requirements for reliable timber structures acoustic predictions are discussed.